A Comparative Study of Metaphors and Metonymies of Russian and Chinese Related to Word "Hand" - Chen, Xi (Journal of Chinese Language and Culture Studies, 2024)
Language comparison is a powerful tool in linguistics. It not only deepens the understanding of the linguistic characteristics of the language being compared, but also helps to analyze the characteristics of cross-language and cross-cultural human thinking. The purpose of this thesis is to supplement the deficiencies of previous studies, conduct a comprehensive comparison of "hand" metaphors and metonyms in Chinese and Russian, use corpus methods to estimate their generality in the two languages, and analyze the Russian language reflected by these metaphors and metonyms. and characteristics of Chinese culture. Literature research method: This paper sorts out the metaphor and metonymy of "hand" in Russian and Chinese on the basis of researching metaphors, idioms, word-formation literature, dictionaries and other materials. This study concludes that first, compared with Russian words for "hand", metonymy and metaphor are more frequently used in Chinese. Second, there are more "hand" word metaphors than metonymy in the Chinese corpus, but there is no big difference in the number of metonymy and metaphor in the Russian corpus. Third, the metonymy of "hand" words in Chinese and Russian is relatively similar, and the difference between metaphors is more obvious, which shows that culture has a greater influence on metaphors, such as the characteristics of the showman's culture, gestures and other non-verbal communication habits, etc.